Emulation of the occam((TM)) parallel programming language - Doherty, B S; Harris, S A J (IEEE transactions on education, 1997)
This paper describes emulation of parallel execution of a program written in standard occam((TM)) source code. The occam language is a high-level language specifically designed to accommodate concurrent programming. The emulator checks and executes most instructions in the occam 2 language, providing a useful tool for debugging simple occam programs, and also provides accessibility to allow monitoring of execution. A "user friendly" graphical interface is an integral part of the emulator. The paper describes the emulator and its use in teaching the occam language and parallel programming concepts to final year undergraduates. The teaching context is given and laboratory notes outlined along with sample programs that illustrate features of the language